Development of an artificial knee joint and ski load simulator for the evaluation of knee braces and mechantronic bindings - Nusser, M.; Senner, V.; Brucker, P. U. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
This setup represents a novel and unique method for realistic testing of physiologic and supra-physiologic loadings in alpine skiing where in vivo testing is not feasible.